Topological and conformational effects on electron transfer dynamics in porphyrin-[60]fullerene interlocked systems - Megiatto, Jackson D.; Schuster, David I.; De Miguel Rojas, Gustavo; Wolfrum, Silke; Guldi, Dirk Michael (Chemistry of Materials, 2012)
The effect of molecular topology and conformation on the dynamics of photoinduced electron transfer (ET) processes has been studied in interlocked electron donor-acceptor systems, specifically rotaxanes with zinc(II)-tetraphenylporphyrin (ZnP) as the electron donor and [60]fullerene (C ) as the electron acceptor. Formation or cleavage of coordinative bonds was used to induce major topological and conformational changes in the interlocked architecture. In the first approach, the tweezer-like structure created by the two ZnP stopper groups on the thread was used as a recognition site for complexation of 1,4-diazabicyclo[2.2.2]octane (DABCO), which creates a bridge between the two ZnP moieties of the rotaxane, generating a catenane structure. The photoinduced processes in the DABCO-complexed (ZnP) -[2]catenate-C system were compared with those of the (ZnP) -rotaxane-C precursor and the previously reported ZnP-[2]catenate-C . Steady-state emission and transient absorption studies showed that a similar multistep ET pathway emerged for rotaxanes and catenanes upon photoexcitation at various wavelengths, ultimately resulting in a long-lived ZnP /C charge-separated radical pair (CSRP) state. However, the decay kinetics of the CSRP states clearly reflect the topological differences between the rotaxane, the catenate, and DABCO-complexed-catenate architectures. The lifetime of the long-distance ZnP -[Cu(I)phen ] -C CSRP state is more than four times longer in 3 (1.03 μs) than in 1 (0.24 μs) and approaches that in catenate 2 (1.1 μs). The results clearly showed that creation of a catenane from a rotaxane topology inhibits the charge recombination process. In a second approach, when the Cu(I) ion used as the template to assemble the (ZnP) -[Cu(I) phen ] -C rotaxane was removed, it was evident that a major structural change had occurred. since charge separation between the chromophores was no longer observed upon photoexcitation in nonpolar as well as in polar solvents. Only ZnP and C triplet excited states were observed upon laser excitation of the Cu-free rotaxane. These results highlight the critical importance of the central Cu(I) ion for long-range ET processes in these nanoscale interlocked electron donor-acceptor systems. © 2012 American Chemical Society.